Efektivitas Program Bantuan Sosial Tunai Di Masa Covid-19 Oleh Dinas Sosial Kota Jakarta Timur (Studi Kasus RW. 013, Kelurahan Malaka Jaya, Kecamatan Duren Sawit, Jakarta Timur) - Rhut Dear Dwigita; Hairani Siregar (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
The Cash Social Assistance Program is a social program as a form of manifestation of Government intervention through the Ministry of Social Affairs of the Republic of Indonesia in order to provide a stimulus for the Social Safety Network in the midst of the Covid-19 period. The Social Assistance Program will be given to the community based on the Integrated Social Welfare Data (DTKS). The emergence of Covid-19 in Indonesia raises concerns from various groups, especially the community and has a detrimental impact on various sectors. As a form of state responsibility to the community in anticipating all problems related to Covid-19, the government distributes various assistance schemes, one of which is the Cash Social Assistance (BST) program. The purpose of this study is to determine how the effectiveness of the cash social assistance program using 4 indicators of Budiani's theory (Targeting Accuracy, Program Socialization, Program Objectives, Program Monitoring) during Covid-19 by the East Jakarta city social service. The method used in this research is a descriptive research method with a qualitative approach. The informants in this study totaled eight people. The informants consisted of two key informants, three main informants, and three additional informants. The results of this study indicate that the implementation of the Cash Social Assistance program during the Covid-19 period in RW.013 Malaka Jaya Village has been effective. The implementation of the cash social assistance program has been carried out well, although there are still weaknesses in the implementation of the program because of the uneven socialization of the program given to residents of RW.013 Kelurahan Malaka Jaya.